Heliopolis 21 - Bruni, Angela Raffaella (AND Rivista di architetture, città e architetti, 2019)
The selected projects, both small and large scale, and the works carried out by Heliopolis 21 testify to the studio’s ability to construct buildings and use space, but also to rework buildings and sets of buildings, to build open land, in other words, they are the symbol of their “architectural” know-how.